Profile of Stroke Patients with COVID-19 at Rumah Sakit Islam Surabaya Jemursari, Indonesia - Syifak, Shobihatus; Yuniati, Dyah; Surya, Prima Ardiansyah; Saffanah, Vena Saskia Prima (Jurnal Medis Islam Internasional, 2023)
Background: Stroke is the number one cause of death in Indonesia, in America stroke is also the number one cause of disability. In COVID-19, most patients experience mild to moderate respiratory symptoms, and need no specific treatment. However, in some patients with comorbidities such as cardiovascular, diabetes mellitus, chronic respiratory disease, and malignancy, it often gives serious manifestation. Objective: This study aimed to profile of stroke patients with COVID-19 at Rumah Sakit Islam Surabaya Jemursari, Indonesia. Method: The type of this research was observational retrospective research. We used all the stroke patient hospitalized at Rumah Sakit Islam Surabaya Jemursari from April to December 2020 that confirmed the diagnosis of COVID-19. We used the general data, data of clinical symptoms, blood pressure, head CT-scan findings, and laboratory findings the data of participants was collected. The data showed as number (frequency) and percentage. Results: The patient’s average age of 57 years, male was common; patients with hypertension were often seen in the comorbidities; ischemic strokes were by far the most prevalent form; subcortical regions were the most frequent location of stroke based on the CT scan. The results of head CT showed that 91.7% of patients had an ischemic stroke and 8.3% of patients had a hemorrhagic stroke. Conclusions: The stroke patients with COVID-19 and hospitalized at Rumah Sakit Islam Surabaya Jemursari, Indonesia have an average age of 57 year, and most of the patient was male. Comorbid hypertension was commonly observed in this study. Based on the type of stroke, ischemic was the most common manifestation and subcortical regions were the most frequent location.